Dual-energy CT for the diagnosis of gout: an accuracy and diagnostic yield study. Issue 6 (25th March 2014) - Bongartz, Tim; Glazebrook, Katrina N; Kavros, Steven J; Murthy, Naveen S; Merry, Stephen P; Franz, Walter B; Michet, Clement J; Veetil, Barath M Akkara; Davis, John M; Mason, Thomas G; Warrington, Kenneth J; Ytterberg, Steven R; et al.
Abstract : Objectives: To assess the accuracy of dual-energy CT (DECT) for diagnosing gout, and to explore whether it can have any impact on clinical decision making beyond the established diagnostic approach using polarising microscopy of synovial fluid (diagnostic yield). Methods: Diagnostic single-centre study of 40 patients with active gout, and 41 individuals with other types of joint disease. Sensitivity and specificity of DECT for diagnosing gout was calculated against a combined reference standard (polarising and electron microscopy of synovial fluid). To explore the diagnostic yield of DECT scanning, a third cohort was assembled consisting of patients with inflammatory arthritis and risk factors for gout who had negative synovial fluid polarising microscopy results. Among these patients, the proportion of subjects with DECT findings indicating a diagnosis of gout was assessed. Results: The sensitivity and specificity of DECT for diagnosing gout was 0.90 (95% CI 0.76 to 0.97) and 0.83 (95% CI 0.68 to 0.93), respectively. All false negative patients were observed among patients with acute, recent-onset gout. All false positive patients had advanced knee osteoarthritis. DECT in the diagnostic yield cohort revealed evidence of uric acid deposition in 14 out of 30 patients (46.7%). Conclusions: DECT provides good diagnostic accuracy for detection of monosodium urate (MSU) deposits in patients with gout. However, sensitivity is lower in patients with recent-onset disease. DECT has a significant impact on clinical decision making when gout is suspected, but polarising microscopy of synovial fluid fails to demonstrate the presence of MSU crystals.